Validation of SOC Estimation Using OC and EC Concentration in PM2.5 Measured at Seoul - Ha Young Yoo; Ki Ae Kim; Yong Pyo Kim; Chang Hoon Jung; Hye Jung Shin; Kwang Ju Moon; Seung Myung Park; Ji Yi Lee (Aerosol and Air Quality Research)
Abstract The organic carbon in the ambient particulate matter (PM) is divided into primary organic carbon (POC) and secondary organic carbon (SOC) by their formation way. To regulate PM effectively, the estimation of the amount of POC and SOC separately is one of the important consideration. Since SOC cannot be measured directly, previous studies have evaluated the determination of SOC by the Elemental Carbon (EC) tracer method. The EC tracer method is a method of estimating the SOC value from calculating the POC by determining (OC/EC)pri which is the ratio of the measured values of OC and EC from the primary combustion source. In this study, three different approaches were applied to OC and EC concentrations in PM2.5 measured at Seoul for determining (OC/EC)pri: 1) the minimum value of OC/EC ratio during the measurement period; 2) regression analysis of OC vs. EC to select the lower 5-20% OC/EC ratio; 3) determining the OC/EC ratio which has lowest correlation coefficient value (R2) between EC and SOC which is reported as minimum R squared method (MRS). Each (OC/EC)pri ratio of three approaches are 0.35, 1.34, and 1.77, respectively from the 1-h data. We compared the (OC/EC)pri ratio from 1-h data with 24-h data and revealed that (OC/EC)pri estimated from 24-h data had twice larger than 1-h data due to the low time resolution of sampling. We finally confirmed that the most appropriate value of (OC/EC)pri is that calculated by a regression analysis of 1-h data and estimated SOC values at PM2.5 of the Seoul atmosphere.